Pengaruh Plyometric Exercise Terhadap Respiratory Rate Pada Pemain Bola Voli Universitas Mercu Buana - Heri Wibisono; Condrowati Condrowati (Jurnal Ilmiah Fisioterapi, 2021)
Introduction: Plyometric exercise is a basic exercise having a characteristic, like a muscle stretch and tendon then followed by shortening. The exercise increases the elasticity of muscle fiber and connective tissues in order to be raised a purpose to increase speed, stability, power, endurance, cardiorespiratory, and agility. Plyometric exercise is able to influence the vital function in the body, such as respiratory rate. The research aims to know the influence of plyometric exercise on the respiratory rate of volleyball players at Mercu Buana University. Method: The research used the one group pre-test-post-test design. The research was conducted to volleyball player group which fulfil inclusion criteria. The sample of the research was 16 volleyball players which were given the plyometric exercise with duration 3times/weeks during 12 weeks with exercise 30minutes/session with aerobic technique. The measurement of respiratory rate was counted by breath frequency on the 1 minute. Result: Based on the Wilcoxon test, there is an influence of plyometric exercise toward the respiratory rate p=0.000 (p<0.05). Conclusion: There is a influence of plyometric exercise to respiratory rate. Keyword : Plyometric Exercise, Respiratory Rate, Volleyball